Targeting the ubiquitin-proteasome system: a novel therapeutic strategy for neuroblastoma - He, Yangshen; Wang, Jianing (Frontiers in Oncology, 2024)
Neuroblastoma (NB) stands as a common and formidable malignant tumor among children, characterized by marked tumor heterogeneity and resistance to conventional treatments. Central to the regulation of protein stability, localization, and function is the process of ubiquitination—a critical protein modification. The therapeutic potential of drugs that target deubiquitination, demonstrated in the treatment of refractory multiple myeloma, warrants investigation in the context of NB. This review endeavors to demystify the intricate biological implications of ubiquitination within NB pathology, synthesize the current landscape of preclinical studies focused on the inhibition of the ubiquitin-proteasome system in NB, and assess the viability of this strategy as an innovative therapeutic frontier.